The Influence of Customer Satisfaction, brand trust and Brand Loyalty on Purchase Intention: A Study of McDonald’s in Malaysia - Kee, Daisy Mui Hung; Sin, Liem Gai; Yuan, Neo Zhan; Ni, Nelly Lau Yenn; Wen, Ng Kar; Fang, Ng Suk; Rayhan, Muhammad; Ali, Muhammad Hasyir; Yose, Joseph Willy; Muhsyi, Ufairoh Aqilah (AIBPM Publisher, 2023)
Customer satisfaction is crucial to the success of any business.It has been studied in the fields of business and marketing since the 1970s. When customers are satisfied, brand loyalty is immediately involved. As a result, brand loyalty has received a lot of attention in recent decades. McDonald's is the world's leading fast service restaurant, with over 36,000 outlets worldwide and more than 70 million customers served daily in more than 100 countries. Every month, McDonald's serves approximately 13.5 million customers in over 320 stores in Malaysia. The company's performance is strongly related to its high levels of brand loyalty and customer satisfaction. This paper aims to examine how customer satisfaction, brand trust and brand loyalty may influence the purchase intention of McDonald in Malaysia. We applied SPSS to test hypotheses, and 150 McDonald's customers engaged in a Google form-based online survey. The findings reveal that customer satisfaction, brand trust and brand loyalty influence McDonald's customers purchasing intentions. Recommendations and implications were discussed.